2020
DOI: 10.1002/adhm.202000794
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Silk Fibroin/Polyurethane Arteriovenous Graft for Hemodialysis: Proof‐of‐Concept Animal Study in an Ovine Model

Abstract: To solve the problem of vascular access failure, a novel semi-degradable hybrid vascular graft, manufactured by electrospinning using silk fibroin and polyurethane (Silkothane), has been previously developed and characterized in vitro. This proof-of-concept animal study aims at evaluating the performances of Silkothane grafts in a sheep model of arteriovenous shunt, in terms of patency and short-term remodeling. Nine Silkothane grafts are implanted between the common carotid artery and the external jugular vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…So far, there are many papers about SF-PU composite materials to use them as biomaterials. 13,25,[28][29][30][31][32][33][34][35][36][37]57,58 commercially available biomedical grade segmented PU by wet spinning method, which has potential as a fiber for artificial vascular graft. 28 The small-diameter tubular artificial vascular graft was prepared from the HFIP solutions of SF-biomedical grade segmented PU mixture by electrospinning method by us.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, there are many papers about SF-PU composite materials to use them as biomaterials. 13,25,[28][29][30][31][32][33][34][35][36][37]57,58 commercially available biomedical grade segmented PU by wet spinning method, which has potential as a fiber for artificial vascular graft. 28 The small-diameter tubular artificial vascular graft was prepared from the HFIP solutions of SF-biomedical grade segmented PU mixture by electrospinning method by us.…”
Section: Discussionmentioning
confidence: 99%
“…The electrospinning methods have been used widely for the application of the SF-PU composite materials in biomedical field. 13,[29][30][31][32] The SF-PU composite films were also prepared by physical blending method. 25,[34][35][36][37]58 The characterization of the SF-PU composite materials by FT-IR and X-ray diffraction analyses suggested that there are no specific interactions between SF and PU, implying molecular immiscibility and phase separation in these materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations